Topology Optimization of Polymer-Based Bending Tools Manufactured via Additive Technology: Numerical and Experimental Validation - Giorleo, Luca; Deniz, Kudret Irem (Journal of Manufacturing and Materials Processing, 2025)
Sheet metal forming is a widely used manufacturing process, but the high cost and long production time of traditional forming tools limit its flexibility, especially for prototyping and small-batch production. Additive manufacturing offers a promising alternative, enabling the rapid and cost-effective fabrication of customized tools. In this study, bending tools were produced using Fused Filament Fabrication and optimized through a topology optimization approach. A combined experimental and numerical approach was applied to validate standard tool geometries and extract load conditions for use in a topology optimization process. The resulting optimized punch and die achieved a mass reduction of approximately 50% while maintaining structural integrity and safety factors well above critical thresholds. Finite Element Analysis revealed an increase in elastic deformation and stress concentration in non-critical regions, without compromising tool functionality. Experimental tests with the optimized tools confirmed their suitability for sheet metal bending, although a decrease of about 2° in the bending angle and an increase in variability were observed, consistent with simulation results. The study demonstrates the feasibility of using topology-optimized polymer tools for low-volume forming applications, offering a lightweight, cost-effective, and sustainable alternative to traditional metal tooling.